Key role played by mesophyll conductance in limiting carbon assimilation and transpiration of potato under soil water stress - Beauclaire, Quentin; Vanden Brande, Florian; Longdoz, Bernard (Frontiers in Plant Science, 2024)
The identification of the physiological processes limiting carbon assimilation under water stress is crucial for improving model predictions and selecting drought-tolerant varieties. However, the influence of soil water availability on photosynthesis limiting processes is still not fully understood. This study aimed to investigate the origins of photosynthesis limitations on potato (Solanum Tuberosum) during a field drought experiment. Gas exchange and chlorophyll fluorescence measurements were performed at the leaf level to determine the response of photosynthesis limiting factors to the decrease in the relative extractable water (REW) in the soil. Drought induced a two-stage response with first a restriction of CO2 diffusion to chloroplasts induced by stomatal closure and a decrease in mesophyll conductance, followed by a decrease in photosynthetic capacities under severe soil water restrictions. Limitation analysis equations were revisited and showed that mesophyll conductance was the most important constraint on carbon and water exchanges regardless of soil water conditions. We provide a calibration of the response of stomatal and non-stomatal factors to REW to improve the representation of drought effects in models. These results emphasize the need to revisit the partitioning methods to unravel the physiological controls on photosynthesis and stomatal conductance under water stress.